Electron paramagnetic resonance and microstructural insights into the thermal behavior of simonkolleite nanoplatelets - Rostas, Arpad Mihai; Kuncser, Andrei Cristian; Ghica, Daniela; Palici, Alexandra; Maraloiu, Valentin Adrian; Vlaicu, Ioana Dorina (Physical chemistry chemical physics : PCCP, 2020)
The aim of this paper is the study of the thermal behavior of the simonkolleite Zn 5 (OH) 8 Cl 2 ·H 2 O (ZHC) by electron paramagnetic resonance (EPR) spectroscopy, in particular. It is well known that during heating ZHC undergoes a complex transformation which involves several overlapping stages. However, with reference to the data reported on this subject, it can be concluded that there is still an ongoing debate regarding the intermediate stages of this process. The data presented in this study support a simple decomposition process of the ZHC prepared using the precipitation method. The EPR data correlated to the data obtained by other experimental techniques, such as XRD, TEM, SEM and EDX, indicate that during the thermal treatment the ZHC suffers a partial decomposition to ZnO with no intermediate products. After annealing at 500 °C for 1 h, a recombination process of ZHC is observed. Moreover, the kinetics associated to these decomposition steps were determined and the evolution of the paramagnetic centers was also followed and studied. This study offers new information related to the thermal behavior of ZHC, especially regarding the EPR data which is reported for the first time on this subject and material. The thermal decomposition process of simonkolleite, at 500 °C was monitored by EPR and electron microscopy. The experimental data indicate that after an 1 h at 500 °C, three morphologies can be observed from the thermal decomposition of ZHC.